Conservatism, Earnings Quality, and Stock Prices - Indonesian Evidence - Krismiaji Krismiaji; Sururi Sururi (Journal of Accounting and Investment, 2021)
Research aims: This research investigates the association of conservatism (both conditional and unconditional) with quality of earnings as well as with stock prices on companies listed on the Indonesia Stock Exchange (IDX).Design/Methodology/Approach: The research uses a sample of 846 observations of publicly listed companies on the Indonesian Stock Exchange for the fiscal year that ends on December 31, 2016 through 2018. Conditional conservatism is measured by using an asymmetric timeliness measure from Basu (ATMB). Net income ratio (CFO/NI) is a proxy for earnings quality whereas ratio between market value and book value (MTB) is a measure of unconditional conservatism. The data used in this study are obtained both from Indonesian Stock Exchange database, and from company annual reports.Research findings: The study finds that all companies analyzed implement conservative accounting policies and practices. Besides, quality of earnings and stock prices are negatively associated with conditional conservatism. This research also proves that stock price negatively associated with unconditional conservatism, whereas unconditional conservatism does not associated with earnings quality.Theoretical contribution/ Originality: This study enriches the existing literature about conservatism, especially in emerging market environment. Moreover, this study discusses a set of conservatism that consist of conditional and unconditional conservatism. This may give a complete picture of conservatism practices adopted by Indonesian companies.Practitioner/Policy implication: Since conservatism can solve agency cost problems, the result of this study may affect the way a company produce useful information for interest parties.Research limitation/Implication: The use of the purposive sampling method limits generalizations, because sample designs could not be assumed to characterize all companies listed on IDX.